Analisis Faktor-Faktor Yang Mempengaruhi Konsumen Dalam Pengambilan Keputusan Pembelian Produk Mie Instan Merek Indomie - Yuhardi yuhardi (Management Studies and Entrepreneurship Journal (MSEJ), 2020)
This study aims to determine and analyze the influence of consumer behavior consisting of cultural, social, personal and psychological factors on the decision to buy indomie brand instant noodle products. To find out among the cultural, social, personal and psychological factors that have a dominant influence on a student's decision to buy indomie brand instant noodles By using multiple linear regression analysis and using a sample of 40 student respondents obtained the following results: From the results of the analysis found that the variables of cultural, social, personal and psychological factors simultaneously / together have a significant (significant) effect on the decision to purchase instant noodle products indomie brand and psychological variables have a dominant influence on the purchase decision of indomie brand instant noodle products. Keywords: Consumer Behavior, Decision Making, Satisfaction